Dominant negative retinoid X receptor beta inhibits retinoic acid-responsive gene regulation in embryonal carcinoma cells. - Minucci, S (1994)
Retinoid X receptors (RXRs) heterodimerize with multiple nuclear hormone receptors and are thought to exert pleiotropic functions. To address the role of RXRs in retinoic acid- (RA) mediated gene regulation, we designed a dominant negative RXR beta. This mutated receptor, termed DBD-, lacked the DNA binding domain but retained the ability to dimerize with partner receptors, resulting in formation of nonfunctional dimers. DBD- was transfected into P19 murine embryonal carcinoma (EC) cells, in which reporters containing the RA-responsive elements (RAREs) were activated by RA through the activity of endogenous RXR-RA receptor (RAR) heterodimers. We found that DBD- had a dominant negative activity on the RARE reporter activity in these cells. P19 clones stably expressing DBD- were established; these clones also failed to activate RARE-driven reporters in response to RA. Further, these cells were defective in RA-induced mRNA expression of Hox-1.3 and RAR beta, as well as in RA-induced down-regulation of Oct3 mRNA. Gel mobility shift assays demonstrated that RA treatment of control P19 cells induces RARE-binding activity, of which RXR beta is a major component. However, the RA-induced binding activity was greatly reduced in cells expressing DBD-. By genomic footprinting, we show that RA treatment induces in vivo occupancy of the RARE in the endogenous RAR beta gene in control P19 cells but that this occupancy is not observed with the DBD- cells. These data provide evidence that the dominant negative activity of DBD- is caused by the lack of receptor binding to target DNA. Finally, we show that in F9 EC cells expression of DBD- leads to inhibition of the growth arrest that accompanies RA-induced differentiation. Taken together, these results demonstrate that RXR beta and partner receptors play a central role in RA-mediated gene regulation and in the control of growth and differentiation in EC cells.